An ultrastable zirconium-phosphonate framework as bifunctional catalyst for highly active CO2 chemical transformation. Issue 7 (9th January 2017) - Gao, Chao-Ying; Ai, Jing; Tian, Hong-Rui; Wu, Dai; Sun, Zhong-Ming
Abstract : An ultrastable zirconium phosphonate as bifunctional catalyst for a CO2 /epoxide coupling reaction exhibits considerably higher activity than most documented MOF catalysts. Abstract : A zirconium-phosphonate network, as a bifunctional catalyst for carbon dioxide (CO2 )/epoxide coupling reaction, exhibits very high activity that is superior to most documented metal–organic framework (MOF)-based catalysts. Furthermore, it possesses extraordinary tolerance to extremely harsh conditions, such as aqua regia . This paper describes the use of metal phosphonate as a new MOF applied to CO2 transformation.